2023
DOI: 10.3389/fonc.2023.1162694
|View full text |Cite
|
Sign up to set email alerts
|

Novel pharmacological and dietary approaches to target mTOR in B-cell acute lymphoblastic leukemia

Abstract: High-risk subtypes of B-cell acute lymphoblastic leukemia (B-ALL) are frequently associated with aberrant activation of tyrosine kinases (TKs). These include Ph+ B-ALL driven by BCR-ABL, and Ph-like B-ALL that carries other chromosomal rearrangements and/or gene mutations that activate TK signaling. Currently, the tyrosine kinase inhibitor (TKI) dasatinib is added to chemotherapy as standard of care in Ph+ B-ALL, and TKIs are being tested in clinical trials for Ph-like B-ALL. However, growth factors and nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…This is expected since the substrates of ASCT2 and SNAT5 play pleiotropic roles in cell metabolism and are involved not only in protein synthesis but also in several other cell pathways, such as mTOR signalling 36,37 . Recently, novel pharmacological and dietary approaches have been proposed to inhibit mTOR activity, which is known to correlate with a poor prognosis in BCP‐ALL positive for the Philadelphia chromosome 38 . In a preliminary experiment, shown in Supplementary Material (Figure S8), both inhibitors GluγHA and V‐9302 have a marked inhibitory effect on the BCR‐ABL‐positive SUP‐B15 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…This is expected since the substrates of ASCT2 and SNAT5 play pleiotropic roles in cell metabolism and are involved not only in protein synthesis but also in several other cell pathways, such as mTOR signalling 36,37 . Recently, novel pharmacological and dietary approaches have been proposed to inhibit mTOR activity, which is known to correlate with a poor prognosis in BCP‐ALL positive for the Philadelphia chromosome 38 . In a preliminary experiment, shown in Supplementary Material (Figure S8), both inhibitors GluγHA and V‐9302 have a marked inhibitory effect on the BCR‐ABL‐positive SUP‐B15 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The third generation of mTOR inhibitors is called RapaLinks or bi-steric mTORC1 inhibitors; these are made by connecting rapamycin and TOR-Ki. This generation embraces the action of both first-and second-generation mTOR inhibitors [84,85].…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…In in vitro research, RMC-4627 demonstrated strong and selective inhibition of 4E-BP1 phosphorylation specifically within B-ALL cell lines, while mTORC2 activity was unaffected. RMC-4627 reduced proliferation, decreased survival, and significantly increased the efficacy and tolerability of Dasatinib in a Ph+ B-ALL xenograft model [85,96]. It is worth adding that the first clinical candidate in the class of bi-steric mTORC1 inhibitor (RMC-5552) is undergoing clinical trials in solid tumors (NCT04774952) [97].…”
Section: Mtor Inhibitorsmentioning
confidence: 99%